1. you know that x=-y+7 so you are going to take that and substitute/put it in for x in the followin equation
(-y+7)-y=-9
2. in this equation we know that y=2x,
4x+3(2x)=20
4x+6x=20 10x=20
divide both sides by ten and you get x=2
3. y=2x+5
3x-2(2x+5)=5
3x-(6x+10)=5
-3x+10=5 subtract 10 from each side
-3x=-5 divide both sides by -3 to get answer
I'm pretty sure I did this right but no guarantees :)
Hope this will help you get the idea
determine the resulting equation if one variable is solved in terms of the other variable in one equation and substitute this variable in the other equation.
1.) x=-y+7
x-y= -9
2.) y=2x
4x +3y=20
3.) y=2x +5
3x-2y=5
1 answer